The Influence of Multimedia Technology on Deep Learning E-Learning Application - Aang Ibnu Ahmad; Seandy Satrio Rianto seandy (Westscience Press, 2024)
In this research we collected data from a number of users of e-learning applications that have different multimedia features. We do this through survey methods and statistical analysis. Multimedia technology has become an important component in e-learning platforms, allowing users to interact with learning materials more dynamically. The research results show that multimedia technology has a significant positive effect on the e-learning user experience. When multimedia is used effectively, users feel more engaged, understand the material better, and are more satisfied with their learning experience. These results indicate that instructors and e-learning platform developers have significant benefits in improving the efficiency of online learning. This research provides useful insights into the role of multimedia technology in enhancing experiences. Keywords: E-Learning Media, Learning Motivation, Learning Media.